2016
DOI: 10.1017/s0008938916000625
|View full text |Cite
|
Sign up to set email alerts
|

“Bad” Politics and “Good” Culture: New Approaches to the History of the Weimar Republic

Abstract: More than thirty years ago, Eberhard Kolb commented that the vast wealth of research on the history of the Weimar Republic made it “difficult even for a specialist to give a full account of the relevant literature.” Since then, the flood of studies on Weimar Germany has not waned, and by now it is hard even to keep track of all the review articles meant to cut a swath through this abundance. Yet the prevailing historical image of the era has remained surprisingly stable: most historians have accepted the maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Caillier, J. G et al demonstrated the impact of the democratic leadership style on citizens and the impact of democratic education on students through a series of questionnaires [15]. Hung et al argued that a good political culture could promote socioeconomic development and also reflect the relationship between politics and culture by studying the history of the Weimar Republic [16]. Yuchtman, N argued that the traditional education system based on Confucian classics has little relevance to modern education and called for modern education to improve ideological education by drawing on good traditional culture [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Caillier, J. G et al demonstrated the impact of the democratic leadership style on citizens and the impact of democratic education on students through a series of questionnaires [15]. Hung et al argued that a good political culture could promote socioeconomic development and also reflect the relationship between politics and culture by studying the history of the Weimar Republic [16]. Yuchtman, N argued that the traditional education system based on Confucian classics has little relevance to modern education and called for modern education to improve ideological education by drawing on good traditional culture [17].…”
Section: Literature Reviewmentioning
confidence: 99%